Transformation of Moderate Religious Values through Islamic Digital Literacy:A Conceptual Study on Islamic Higher Education - Akmal Badruzzaman; Riky Supratama (Al-Ulum: Jurnal Pendidikan Islam, 2026)
This study aims to formulate the contribution of Islamic digital literacy components to the internalization of religious moderation, identify the role of institutional factors as mediators, and develop a conceptual model that describes the mechanism of value transformation in IHEI students. The approach used is qualitative research based on a literature study of 22 empirical and conceptual articles, major theoretical books, and policy documents analyzed through content analysis and thematic analysis. The results show that information verification skills, religious hermeneutic abilities, media ethics, and content production participation are the main components of digital literacy that contribute to the formation of moderate religious attitudes. The findings also show that the PAI curriculum, the House of Religious Moderation, and student communities play a significant role in directing the process of value transformation from exposure to digital content to inclusive religious practices.